KONSEP DASAR TEORI BATASAN: TELA’AH PEMIKIRAN M. SYAHRUR DALAM METODOLOGI FIQH ISLAM KONTEMPORER - Fermadi, Bayu (JURNAL ISLAM NUSANTARA, 2018)
Shahrur's anxiety began with the cessation of the understanding of the muhkamat verses which should continue to develop in accordance with the times, according to Syahrur that understanding was influenced by the thoughts of the previous scholars who were still shackled from the traditional Fiqh concept. against the Qur'an and Hadith with a hermenetic approach, and linguistic. In redefining laws relating to humans, Shahrur does not use qiyas and ijma 'of the scholars, so understanding the Qur'an is purely a textual approach. Syahrur believes that there is no synonymity in at Tanzil, so that each text stands alone and has its own meaning. Whereas the Sunnah is the first form of understanding of the Prophet Muhammad, in other words that the understanding of the prophet is the first step towards understanding the Qur'an and the opening of subsequent understandings in accordance with the context and age at which Tanzil is located.